2006
DOI: 10.3171/spi.2006.5.1.9
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and radiographic outcomes of thoracic and lumbar pedicle subtraction osteotomy for fixed sagittal imbalance

Abstract: Object he authors conducted a study to evaluate the radiographically documented and functional outcomes obtained in patients who underwent pedicle subtraction osteotomy (PSO). They also compared outcomes after classification of cases into thoracic and lumbar PSO subgroups. Methods he authors analyzed data obtained in 35 consecutive PSO-treated patients with sagittal imbalance. One surgeon performed all s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
109
1
6

Year Published

2008
2008
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 187 publications
(124 citation statements)
references
References 25 publications
8
109
1
6
Order By: Relevance
“…Several authors reported that after VCR and spine shortening, the spine should be fused anteriorly with titanium meshwork implant and bone chips autografts to maintain long-term fusion [27,37]. We grafted autologous bone chips into latero-anterior intervertebral spaces and iliac bone sticks into posterior interspaces, which led to satisfactory fusion and long-term stability as demonstrated by the follow-up, and no pseudarthroses and neurological damage were found in any of the 13 patients.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…Several authors reported that after VCR and spine shortening, the spine should be fused anteriorly with titanium meshwork implant and bone chips autografts to maintain long-term fusion [27,37]. We grafted autologous bone chips into latero-anterior intervertebral spaces and iliac bone sticks into posterior interspaces, which led to satisfactory fusion and long-term stability as demonstrated by the follow-up, and no pseudarthroses and neurological damage were found in any of the 13 patients.…”
Section: Discussionmentioning
confidence: 88%
“…Adult severe rigid congenital kyphoscoliosis has been a persistent and perplexing problem [19,20,27,37]. The operative or nonoperative treatments often fail, resulting in a three-dimensional deformity at coronal, sagittal, and frontal planes [2,16,29,30].…”
Section: Discussionmentioning
confidence: 99%
“…In order to decrease the risk of neurological deficits, the authors recommended central canal enlargement, careful osteotomy closure to prevent or limit subluxation across the osteotomy site, performing a wake-up test after osteotomy and examining all motor functions following surgery. Incidence of neurological injury in the series of Yang et al [20] and Ahn et al [21] was 3.6 and 12 %, respectively.…”
Section: Ponte Osteotomy Smith-petersen Osteotomy (Spo)mentioning
confidence: 95%
“…3 Application of the 3CO techniques, specifically VCR and PSO, for thoracic deformity correction has been described elsewhere. 12,16,28,29 In this cohort of 38 patients, significant reciprocal improvements in cervical parameters were again absent, but as regards the lumbar parameters, there was -7.8° in LL. The explanation for the lack of reciprocal change in CL remains unclear.…”
Section: Spinopelvic Radiographic Outcomesmentioning
confidence: 98%